Advantages of BIM-modeling in the investment and innovation sector in the context of digital transformations of the industry - N. V. Vozgoment; O. E. Astafyeva (Вестник университета)
Approaches to the use of BIM-modeling in construction, methods of its implementation, standardization of parameters of investment activity of projects and its stages are considered. The key points in the organization of digital management at the enterprise were highlighted. The digital experience of foreign countries on the introduction and development of BIM-technologies in construction and the main advantages of the introduction of digital technologies in construction are considered. It is revealed that the digital transformation in the construction industry requires the creation of an appropriate institutional environment and the organization of its functioning in the general digital ecosystem. The concept of a functioning BIM environment with a digital environment is proposed as a part of the implementation of investment project activities in construction.